The Level of Community Participation in Tsunami Disaster Management in Pandeglang District, West Java, Indonesia - Siswo Hadi Sumantri,; Anwar Kurniadi,; Endro Legowo,; Sutawidjaya, Ahmad hidayat (Technium Social Sciences Journal, 2020)
Currently, the biggest incidence of disasters caused 426 people’s death in West Java is tsunami in the coast of Sunda Strait. One of the causes is unsuitable coastal layout managements. The participation of community in disaster management is needed to accelerate the recovery situation. The purpose of this study is to determine the level of the Pandeglang’s community participation in recovering tsunami disasters. The method of the research is qualitative with description design. The results are the communities of Pandeglang District, the village’s head and the district’s head had had the collaboration how to involve the participation in disaster management of tsunami disaster starting from: 1) preparedness and mitigation program were starting from making planning program until finishing it, at the pre-disaster period; 2) communities have participated in making post commands, helping in evacuation of the disaster’s victims and distributing many kinds of relief materials to the disaster’s victims actively at the emergency response response; 3) most of the disaster’s victims had collaborated to occupy the temporarily shelters and followed the back to normal life programs, at the post disaster period. Although the participation of Pandeglang community was not going as well as the Pandeglang Administration’s District suggestions, but the important thing is most of them had participated actively. The conclusions of this research are: 1) the community participated and embroiled on the pre-disaster period, emergency response, and post-disaster period; 2) the level of the community’s participation in Pandeglang District had achieved on acting together levels.